2018
DOI: 10.1152/ajpgi.00334.2017
|View full text |Cite
|
Sign up to set email alerts
|

Complement Factor D protects mice from ethanol-induced inflammation and liver injury

Abstract: Complement plays a crucial role in microbial defense and clearance of apoptotic cells. Emerging evidence suggests complement is an important contributor to alcoholic liver disease. While complement component 1, Q subcomponent (C1q)-dependent complement activation contributes to ethanol-induced liver injury, the role of the alternative pathway in ethanol-induced injury is unknown. Activation of complement via the classical and alternative pathways was detected in alcoholic hepatitis patients. Female C57BL/6J [w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 56 publications
1
46
0
Order By: Relevance
“…For example, complement activation via the alternative pathway is critical to the removal of injured and dying hepatocytes in models of both fibrosis and early ASH. 82,83 MicroRNA, EVs MicroRNAs (miRNAs), small non-coding RNA molecules of 19-25 nucleotides, can induce RNA silencing and regulate gene expression at posttranscriptional levels, playing important roles in a variety of cellular functions. Recent studies have demonstrated that many miRNAs are involved in directly or indirectly regulating inflammatory pathways in ASH.…”
Section: Complementmentioning
confidence: 99%
“…For example, complement activation via the alternative pathway is critical to the removal of injured and dying hepatocytes in models of both fibrosis and early ASH. 82,83 MicroRNA, EVs MicroRNAs (miRNAs), small non-coding RNA molecules of 19-25 nucleotides, can induce RNA silencing and regulate gene expression at posttranscriptional levels, playing important roles in a variety of cellular functions. Recent studies have demonstrated that many miRNAs are involved in directly or indirectly regulating inflammatory pathways in ASH.…”
Section: Complementmentioning
confidence: 99%
“…The overall cellularity of adipose consists of adipocytes and the stromal vascular fraction, including perivascular cells, vascular endothelium, stem cells, pre-adipocytes and immune cells ( 1 , 47 ). Because ethanol activates complement to generate anaphylatoxins ( 8 , 18 ), known activators of the innate immune system, we hypothesized that adipose SVCs, including macrophages, would be the major contributor to ethanol-induced adipose inflammation in mALD. Despite high C5aR1 expression on SVCs compared to adipocytes, data from bone marrow chimeras suggest that C5aR1 expression on cells of non-myeloid origin, likely adipocytes, are the major contributor to the induction of inflammatory responses caused from ethanol feeding in adipose (Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…This is of particular interest for alcohol-mediated pathologies, as gut-derived LPS can stimulate multiple components of the innate immune system and perpetuate systemic inflammation. Indeed, peripheral C5a ( 8 ) as well as circulating endotoxin is increased in ALD patients ( 48 , 49 ). Here we find that ethanol feeding, directly via the activation of complement, stimulates spontaneous secretion of multiple mediators, including chemokines (MCP-1 and chemerin), adipokines (LCN2) and pro-inflammatory cytokines (TNFα) from isolated adipocytes in a C5aR1-dependent manner (Figures 4 , 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations